MODELING IMMISCIBLE FLUID DISPLACEMENT IN A POROUS MEDIUM USING LATTICE BOLTZMANN METHOD - Atykhan, Magzhan; Kabdenova, Bagdagul; Monaco, Ernesto; Rojas-Solórzano, Luis R. (Fluids, 2021)
The numerical investigation of the interpenetrating flow dynamics of a gas injected into a homogeneous porous media saturated with liquid is presented. The analysis is undertaken as a function of the inlet velocity, liquid–gas viscosity ratio (D) and physical properties of the porous medium, such as porous geometry and surface wettability. The study aims to improve understanding of the interaction between the physical parameters involved in complex multiphase flow in porous media (e.g., CO2 sequestration in aquifers).
Keywords: multiphase flow; Lattice Boltzmann Method; Peng–Robinson; capillary number; viscosity ratio; surface wettability